Wheel of coplas and worlds of experience in the gorge and the eastern valleys of Jujuy - Sánchez, Radek (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
The wheels of coplas in the gorge and the eastern high valleys of Jujuy are a type of song accompanied by cajas (drums), typical of the summer season. They begin with a celebration for the deceased and continue active until the funeral of the carnival. With this article I want to offer some reflections on the wheel as a creative and social activity, that "encourages" or "that drives away sadness". From my field experience, the narratives of copleras and copleros and the analysis of vernacular coplas, I will analyze the characteristics of entry into the wheel, which imply, according to general consideration, a break with the common sense of everyday life. In these circumstances, the senses can respond in unpredictable ways, which means the search for new knowledge and resources that allow participants to give meaning to this new order of things, ephemeral, but highly desired. In these cases, through sonorous climates and alcohol intake, where the singularity of the body is confused with the organic nature of the wheel, dissident discourses and a loss of the sense of time can occur, while still insisting on the search for generating joy and beauty.